Notes about Possessing a Heritage in a Komi Village - Art Leete (Journal of Ethnology and Folkloristics)
In this article I try to analyse some aspects of heritage management in the Turya village of the Republic of Komi, Russia. I attempt to demonstrate how the local museum curator, Olga Shlopova, treats her fairy tales, museum exposition and collection of local heritage. My aim is to interpret some dialogue situations between local village people, scholars and officials which indicate how people manage differences in understanding of heritage administration. I presume that local people’s ideas and methods of dealing with cultural phenomena and institutions may obtain their own specific value in the course of culture processes. The question is, how flexible can official cultural specialists be in adapting and reflecting these, sometimes, slightly unconventional approaches. I suppose that an ethical approach helps a researcher to distance him or herself from possible prejudices or, at least, to be more conscious about stereotypes or pre-settled patterns of thinking. Unconditional recognition of an indigenous way of understanding local phenomena also helps a researcher to reach a more culture-specific model of interpretation.